Research publications to Indian Journal of Cancer: a scientometric analysis. Issue 3 (29th April 2014) - Santhanakarthikeyan, S.; Grace, M.; Jeyshankar, R.
Abstract : Purpose: – The aim of the present study is to analyze the literature growth, author productivity, authorship pattern, average length of articles and country collaboration of cancer research in India. The Indian Journal of Cancer, which shows the progress of ontological sciences in India, was established in 1963. Indian Journal of Cancer is the first and only periodical serving the needs of all the specialties of oncology in India. The journal is the official publication of the Indian Cancer Society and Indian Society of Oncology. Design/methodology/approach: – Thirty-nine issues of the Indian Journal of Cancer, published between 2003 and 2012, have been considered for the study. The collected data were recorded in an Excel spreadsheet and analyzed to find the degree of collaboration (DC) between authors, collaboration between countries and authorship pattern. Since the journal publishes research articles, review articles, editorials, letters to the editor, symposiums, forewords, case reports and special articles, only the 244 research articles published during 2003-2012 have been taken into consideration in this study. Findings: – The study revealed that multi-authored papers were more common and that the average length of articles was 5-6 pages. Twenty-two countries contributed papers to this journal during the study period. Additional research is needed to assess the impact of diverse dietary habits, religious practices and lifestyles on the prevention of cancer. Originality/value: – More than 50 per cent of the world's cancer burden, in terms of both numbers of cases and deaths, occurs in developing countries and is rising. By 2020, it is estimated that 70 per cent of all cancer cases will be in these lower-income countries, and approximately one-fifth of these will be in India, with its (still increasing) population of over a billion. While research is necessary to inform effective programs, it is also time to move beyond research to act by implementing programs in cancer prevention and treatment. Cancer is disturbing the growing economy of the country, which can be saved by proper handling of this disease.